Study of Bond Properties of Steel Rebars with Recycled Aggregate Concrete. Experimental Testing - Rafi, M.M. (Проблемы прочности, 2018)
Recycling of concrete can provide an effective solution for waste management. This study investigates the interfacial bond stress versus slip response of steel bars embedded in recycled aggregate concrete. The bond tests were conducted using concentric pullout specimens. The specimens made from natural aggregate concrete were used as control specimens. Three rebar diameters, two rebar types (hot-rolled deformed and cold-twisted ribbed), and three levels of replacement of recycled aggregates (RA) were considered. The bar embedment length was taken as 5 times the bar diameter. The 12 mm-diameter bar exhibited the highest interfacial bond strength, which decreased with the bar diameter. The bond behavior of bars was nearly unaffected by the concrete type for the levels of RA replacement considered. The cold-twisted ribbed bars demonstrated a stiffer post-peak interfacial bond stress-slip response, as compared to hot-rolled deformed bars. Переработка бетона является одним из эффективных решений проблемы утилизации строительных отходов. Исследуется изменение адгезионных напряжений на стыке стальных арматурных стержней с матрицей из переработанного бетона в зависимости от величины проскальзывания между ними. Адгезионные испытания на растяжение проводились на концентрических образцах. Образцы с наполнителем из стандартного бетона использовались в качестве контрольных. Исследовались арматурные стержни двух типов (горячекатаные деформированные и холоднокрученные ребристые) с разными диаметрами и разной долей добавки переработанного бетона. Длина заделки стержней пятикратно превышала их диаметр. Стержни диаметром 12 мм имели наивысшую прочность межфазного сцепления/ адгезии, которая уменьшалась с увеличением их диаметра. Величина доли добавки переработанного бетона практически не влияла на адгезионную прочность стержней. При этом реакция холоднокрученных ребристых стержней по достижении пика адгезионных напряжений в зависимости от проскальзывания оказалась более жесткой, чем горячекатаных деформированных стержней. Переробка бетону є одним з ефективних розв язків проблеми утилізації будівельних відходів. Досліджується зміна адгезійних напружень на стику стальних арматурних стрижнів із матрицею з переробленого бетону залежно від величини проковзування між ними. Адгезійні випробування на розтяг проводились на концентричних зразках. Зразки з наповнювачем зі стандартного бетону використовували як контрольні. Досліджувались арматурні стрижні двох типів (гарячекатані деформовані і холоднокручені ребристі) із різним діаметром і різною долею домішки переробленого бетону. Довжина защемлення стрижнів у п ять разів перевищувала їх діаметр. Стрижні діаметром 12 мм мали найвищу міцність міжфазового зчеплення/адгезії, яка зменшувалась зі збільшенням їх діаметра. Величина долі домішки переробленого бетону практично не впливала на адгезійну міцність стрижнів. При цьому реакція холоднокручених ребристих стрижнів після досягнення піка адгезійних напружень залежно від проковзування є більш жорсткою, ніж гарячекатаних деформованих стрижнів.